1987
DOI: 10.1136/bmj.294.6571.531
|View full text |Cite
|
Sign up to set email alerts
|

Moderate sodium restriction with angiotensin converting enzyme inhibitor in essential hypertension: a double blind study.

Abstract: Fifteen unselected patients who had essential hypertension and whose average supine blood pressure when they were not receiving any treatment and their usual sodium intake was 162/ 107 mm Hg were treated with captopril 50 mg twice daily. After one month's treatment their supine blood pressure had decreased to 149/94 mm Hg. They were then instructed to reduce their sodium intake to about 80 mmol(mEq)/day. After two weeks of moderate sodium restriction they were entered into a double blind randomised crossover s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…This increase in angiotensin II can be blocked by the addition of an inhibitor of the reninangiotensin-aldosterone system 18 so that blood pressure then becomes much more dependent on sodium and water balance. This concept was supported by two previous studies in which it was found that in patients with essential hypertension in whom the renin system is blocked by captopril 6 or enalapril, 7 moderate sodium restriction results in a further fall in blood pressure. Furthermore, with sodium restriction alone, there is no relation between changes in sodium balance and the degree to which blood pressure falls, 1 -3 whereas when the renin system is blocked, the change in blood pressure is significantly correlated with the change in dietary sodium intake.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This increase in angiotensin II can be blocked by the addition of an inhibitor of the reninangiotensin-aldosterone system 18 so that blood pressure then becomes much more dependent on sodium and water balance. This concept was supported by two previous studies in which it was found that in patients with essential hypertension in whom the renin system is blocked by captopril 6 or enalapril, 7 moderate sodium restriction results in a further fall in blood pressure. Furthermore, with sodium restriction alone, there is no relation between changes in sodium balance and the degree to which blood pressure falls, 1 -3 whereas when the renin system is blocked, the change in blood pressure is significantly correlated with the change in dietary sodium intake.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, with sodium restriction alone, there is no relation between changes in sodium balance and the degree to which blood pressure falls, 1 -3 whereas when the renin system is blocked, the change in blood pressure is significantly correlated with the change in dietary sodium intake. 6 Treatment with angiotensin converting enzyme inhibitors alone does not always control blood pressure in patients with moderate-to-severe essential hypertension. The addition of a thiazide diuretic to angiotensin converting enzyme inhibitor treatment has been shown to be effective in reducing blood pressure to the desired range in many patients with more severe essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,24 Evidence suggests that lowering salt intake will be of benefit in CKD, reducing proteinuria and urinary albumin excretion, as well as enhancing the antiproteinuric and antihypertensive effects of blockers of the renin-angiotensin system. 25,26 A recent review of interventional studies in CKD concluded that there was evidence that salt reduction lowered blood pressure in patients with CKD, but acknowledged that there was an overall lack of studies in this patient group.…”
Section: Salt and The Kidneymentioning
confidence: 99%
“…The study demonstrated an approximate 9% fall in blood pressure with moderate salt restriction when on captopril and this fall in blood pressure was significantly related to the reduction in urinary sodium excretion but not the severity of the blood pressure. Overall the study suggested that the combination of an angiotensin-enzyme inhibitor with a moderate but practical reduction in salt intake could be very effective in controlling blood pressure in many patients with essential hypertension (MacGregor et al, 1987). I…”
Section: Introductionmentioning
confidence: 99%